Analyzing the Quality English Translation for Second Language Learners - Hammas Hidayatullah, Muhammad; Mulyadi, Dodi; Hardiyanti, Diana (Universitas Muhammadiyah Semarang, 2024)
The current research investigates the risk-taking characteristics of fourth-semester students at Muhammadiyah University in Semarang and fourth-semester English students at Sanata Dharma University. The participants in this research were 32 fourth-semester students, 6 of whom were second-language students from Sanata Dharma University via Google Fromulir with an English translation written test and Indonesian for the next part of the research. They then received a risk-taking personality questionnaire and a translation test. The research results found that there were errors in sentence structure when translating and incorrect vocabulary. This includes the use of translation models with multiple possible solutions, the development of mediation skills, and the integration of functional linguistics into translation teaching. In addition, this article uses the FAR model, which is an interlanguage translation text quality assessment model that evaluates the quality of translated texts in three areas: functional equivalence, acceptability, and readability. Therefore, EFL students need to master structure and vocabulary to better improve their translation products